Sustainable rural development – EU agricultural perspective - Borec, Andreja; Turk, Jernej (Journal for Geography, 2009)
Rural areas are diverse worldwide but the paradigm of sustainable development and the improving of rural development has become an issue that occupies most of the world’s governments. The global goal is the same everywhere: to improve the well-being of rural people in the broadest possible sense, but the strategies are various and depend on many different factors and sectors. Throughout history, agriculture has always played a dominant role in the development of rural areas, but today its significance is under discussion in many countries. The EU’s Common Agricultural Policy (CAP) has shifted from supporting agricultural production to supporting producers' income directly and with the objective of sustainable agriculture. Issues such as environmental sustainability, the viability of rural economies, food quality and animal health and welfare standards have become more prominent. In this paper, we try to review some key milestones and dates of CAP and to explain the new role for agriculture in rural areas through the concept of multifunctional agriculture. Multifunctionality is therefore argued as a model to bring post-modern agriculture up to speedwith new societal demands. It emphasizes that, in addition to producing food and fiber, agriculture also produces a wide range of non-commodity goods and services, shapes the environment, affects social and cultural systems and contributes to economic growth. Although the concept is rather simple, its translation into policies remains, however controversial (Dobbs and Pretty, 2004) it may be. Thus, the need for further theoretical and empirical research support for deconstructing the multifunctional concept is crucial for sustainable agriculture and rural development in the near future.
Keywords: sustainability; development; agriculture; multifunctionality